2006
DOI: 10.1177/1748895806062982
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the role of the appropriate adult in England and Wales

Abstract: The definition of the role of the ‘appropriate adult’ for young suspects in the Police and Criminal Evidence Act 1984 Code of Practice C is ambiguous and contradictory. This article argues that the role has been socially constructed by the legislator, the courts, young people, the police and appropriate adults themselves. Following various recommendations to use volunteers as appropriate adults, this article revisits the nature of the role in light of a case study of a volunteer appropriate adult service. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
(25 reference statements)
1
26
0
Order By: Relevance
“…The literature has suggested that current provisions could be amended to allow a parent to be present during the process as well as an independent, properly trained practitioner, whether that person is a volunteer or social worker (Littlechild 1995, Pierpoint 1999, 2000a, 2000b, 2006a. However, parents and relatives may have very different views.…”
Section: Journal Of Social Welfare and Family Law 147mentioning
confidence: 95%
See 3 more Smart Citations
“…The literature has suggested that current provisions could be amended to allow a parent to be present during the process as well as an independent, properly trained practitioner, whether that person is a volunteer or social worker (Littlechild 1995, Pierpoint 1999, 2000a, 2000b, 2006a. However, parents and relatives may have very different views.…”
Section: Journal Of Social Welfare and Family Law 147mentioning
confidence: 95%
“…Hodgson 1997, White 2002, volunteer appropriate adults (e.g. Pierpoint 2001Pierpoint , 2006aPierpoint , 2008 and paid appropriate adults could remain, particularly as the 'adequate training' referred to in the proposals (listed in Figure 1) is not part of a national programme for all types of appropriate adult.…”
Section: Journal Of Social Welfare and Family Law 147mentioning
confidence: 97%
See 2 more Smart Citations
“…19 If there are long delays while children and young people wait for an appropriate adult, then the thought of there being further delays could discourage them from requesting legal advice (Dixon et al, 1990). 20 The difficulties encountered with appropriate adults, particularly in relation to access to legal advice, have led some critics to argue for a tightening up of legal protections, including for some, introducing mandatory legal advice for juveniles detained in police stations (Littlechild, 1998;Pierpoint, 2006;Kemp, 2010;Sanders, Young and Burton, 2010). However, it is important that both welfare and legal protections required for juveniles do not unduly increase their time spent in custody.…”
Section: The Role Of Appropriate Adultsmentioning
confidence: 99%